(untitled) (Journal of Engineering Science, 2022)
Fe82Si8B10 amorphous ribbon which containing 82% of Fe and 18% of B and Si were prepared using rapid solidification technique. The samples were constantly annealed for 1 hour in the temperature range of 350°C-600°C. X-ray diffraction analysis (XRD) displays a large peak which is the diffusion hallow suggesting the amorphousity in its origin and formation of crystalline phase with the increment of annealing temperature at 450oC. The magnetic ordering of the ribbon is determined as temperature functions by both AC and DC magnetization. At 450°C, the saturation magnetization (Ms) was found 143 emu/gm and with better value of real part of initial permeability at 450°C as well as better relative quality factor (RQF) was observed at the same temperature. The results are explained as due to higher heating rates than this Si diffuse in amorphous and lost the soft magnetic properties. Journal of Engineering Science 13(1), 2022, 1-8